TUHAN YAHUDI VIS A VIS TUHAN ISLAM: Pembacaan Kritis atas Teks Taurat dan Al-Quran - Lukman Hakim Husnan (Al-Dirayah, 2018)
Compared to Christianity, there are some similarities between Jews and Islam. In addi-tion that both put emphasis on the law, Jews and Islam are two equally representative traditions - or at least claim - as the heir of monotheism that was proclaimed by Abraham. This article cap-tures some of the theological aspects (divinity) from the point of a critical study of the texts of the scriptures for both traditions (Taurat and Qur'an).